Linking Entrepreneurship Education With Entrepreneurial Intentions Of Technical University Students In Ghana: A Case Of Accra Technical University - Nyarko, Cynthia Oduro; Taylor-Abdulai, Hannah Benedicta; Ohene Afriyie, Emelia; Sarpong, Emelia; Ampofo Ansah, Christine (Archives of Business Research, 2017)
Entrepreneurship education is essential to the development and promotion of entrepreneurial intentions among tertiary students. The aim of this study was to examine the relative importance of entrepreneurship education and entrepreneurial intentions among Technical University students, and to determine if there existed relationship between entrepreneurship education and entrepreneurial intentions of students in Technical Universities using Accra Technical University. The issue that the Technical Universities as a Technical, Vocational, Education and Training (TVET) institution is strategically involved in the attainment of the post-2015 SDGs in Ghana by creating an enabling environment (through teaching and learning) for business start-ups among its graduates due to the higher unemployment rate in Ghana. The study is quantitative in nature and adopts the descriptive survey approach by using structured questionnaire and interviews. Stratified and simple random sampling techniques were used to select students from final year classes based on the population from selected departments of the various Schools in the Technical University to form the sample size. In addition, all entrepreneurship lecturers were interviewed. Data analysis was by descriptive statistics using SPSS and regression analysis. The result suggests a positive relationship between entrepreneurship education and entrepreneurial intentions. For policy implication, a more systematic approach to entrepreneurship education is needed to improve the quality of teaching and learning of entrepreneurship in the Technical Universities to promote entrepreneurial intentions among students.